The Constitutional Position of the President and Vice Pres-ident in Indonesia - Abdul Haris; Muhammad Awaluddinul Akbar; Muhammad Kandriana; Muslimin Muslimin; Muhammad Wildan; Erham Erham (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the constitutional position of the President and Vice President in Indonesia following the four amendments to the 1945 Constitution between 1999 and 2002, focusing on how these reforms reshaped executive authority and accountability. It addresses the problem of excessive presidential dominance and unclear vice-presidential functions under the New Order regime, with research objectives to analyze the institutional, authority, accountability, and relational dimensions of the amended constitutional framework. Employing a normative doctrinal method through statute and conceptual approaches, the study analyzes primary legal texts, scholarly articles, and tertiary materials using descriptive-analytical techniques. The main findings reveal that the introduction of direct joint elections, strict two-term limits, impeachment mechanisms, and the establishment of the Constitutional Court significantly strengthened checks and balances, clarified the Vice President’s supportive and succession roles, and redistributed legislative powers to the DPR. These reforms created a more balanced separation of powers and enhanced democratic legitimacy while also highlighting emerging challenges in institutional capture and democratic backsliding. In conclusion, Indonesia’s gradualist constitutional reform successfully transformed an authoritarian executive into a more accountable presidential system, though ongoing vigilance and potential further amendments are necessary to consolidate democratic gains.